Faktor Penyebab Tingginya Kasus Positif COVID-19 Pada Perawat Ruangan Pinere di Rumah Sakit Daerah Madani Kota Pekanbaru - Suryani Arif; Santoso Santoso; M Kamali Zaman (Jurnal Kesehatan Komunitas, 2023)
Background: Pekanbaru Madani Hospital is one of the patient referral hospitals that serve the treatment of patients who are confirmed positive for COVID-19. The increasing number of confirmed cases of COVID-19 patients who have been served by the hospital will have a major impact on the work guidelines and workload of health workers. The number of patients who have been served due to COVID-19 cases was 352 people in 2020 while health workers working at the Madani Regional Hospital confirmed COVID-19 until September 2021. Objective: To find out the factors causing the high number of positive COVID-19 cases in Pinere Room nurses. at the Madani Regional Hospital, Pekanbaru City  Method: quantitative with an analytical survey research type design cross-sectional with collection technique with purposive sampling. The study was conducted in August – September 2021 at the Madani Hospital, the research sample was a total sampling technique of 91 nurses. Collecting data through Google form with univariate analysis, bivariate using chi-square, and multivariate analysis using multiple logistic regression. Research Results: The proportion of nurses who were confirmed positive for COVID-19 was 15 people (16.5%) with bivariate analysis there was a relationship between the use of PPE, application of health protocols, work stress, and work shifts with positive confirmed cases of COVID-19 in nurses. While the results of the multivariate analysis showed that there was a causal relationship between the use of PPE (p-value = 0.009;) and work stress (p-value 0.028) variables that did not have a causal relationship between health protocols (p-value = 0.85) and work shifts (p-value = 0.121). Conclusion: The dominant variable influencing positive confirmed cases of COVID-19 at Madani Hospital is the use of Personal Protective Equipment. Suggestion: Improve the supervisory function of nurses who use PPE when working each shift.